[Some liked it hot in 1852: a booklet about the Stigliano thermal springs (Canale Monterano, Rome)] - Alessio Argentieri; Giuseppe Capelli; Giovanni Rotella; Roberto Mazza (Acque Sotterranee)
[Article in Italian]